Abuse of Guardianship in Criminal Justice - Darti, Andi; Sulaiman, Abdullah (Greenation Publisher & Yayasan Global Resarch National, 2025)
Guardianship (curatele) aims to protect individuals who are legally declared incompetent in exercising their rights and obligations, as stipulated in Article 433 of the Indonesian Civil Code. However, in criminal proceedings, guardianship status is often misused by suspects as a strategy to evade legal processes, even without valid medical grounds. This issue arises due to the absence of clear regulations governing guardianship within the criminal law framework, leading to a legal vacuum and opening avenues for manipulative practices that amount to obstruction of justice. This study adopts a normative juridical approach and literature review to analyze the misuse of guardianship status and the urgency of establishing new regulations that set objective standards for medico-legal evaluation. The findings indicate that weak coordination between law enforcement and medical institutions, as well as the lack of integrative evaluation standards, contributes to the misuse of guardianship. Therefore, firm regulations and cross-sectoral evaluation mechanisms are needed to ensure that guardianship is granted solely to individuals who genuinely require it and not misused as a shield from criminal liability.